Epidemiology of Renal Replacement Therapy in Macedonia - Olivera Stojceva-Taneva (Biomolecules & Biomedicine, 2010)
The purpose of the study is to give an overview of end-stage renal disease (ESRD) and renal replacement therapy (RRT) in the Republic of Macedonia in a period of 6 years (2002-2007). Data are collected by questionnaires for individual patients that are distributed to 18 haemodialysis centres in the country. Incidence, prevalence, mean and median age, primary renal disease, established therapy, number of renal transplants per year and mortality are assessed and elaborated. There is an increase of incident patients on RRT over the years, from 75,5 in 2002 to 99,5 per million population in 2007, on day 91, adjusted for age and gender. Mean age of incident patients is also increasing, from 55,2±14,0 at day 91 in 2002, to 57,5±14,2 in 2007. Hypertension and diabetes are increasing and have become the leading cause of renal failure in incident patients at day 91, unadjusted, in 2007 (26,8 and 21,4% respectively). Prevalent counts on RRT are also increasing, from 559,2 per million population in 2002, adjusted for age and gender, to 767,4 in 2007. Glomerulonephritis and unknown cause of renal failure are the leading cause of ESRD in prevalent patients. Haemodialysis is the predominant RRT modality in Macedonia either for incident, or prevalent patients, and is around 90%. The crude death rate on dialysis is relatively low, 12,5% in 2006. Incidence and prevalence on RRT are continuously increasing, and hypertension and diabetes are becoming the leading cause of ESRD. Kidney transplantation is underrepresented and efforts should be undertaken for its increase.